For a given input value xxx, the function fff outputs a value yyy to satisfy the following equation. y+6=5(x-4)y+6=5(x−4)y, plus, 6, equals, 5, left parenthesis, x, minus, 4, right parenthesis Write a formula for f(x)f(x)f, left parenthesis, x, right parenthesis in terms of xxx. f(x)=f(x)=f, left parenthesis, x, right parenthesis, equals

Respuesta :

Answer:

f(x) = 5x − 26

Step-by-step explanation:

y + 6 = 5(x − 4)

y + 6 = 5x − 20

y = 5x − 26

f(x) = 5x − 26

The function in standard notation is given by:

y = f(x) = 5x - 26

How to write the equation as a function?

Here we have an equation:

y + 6 = 5*(x - 4)

And we want to write this as a function, which means, of the form:

y = f(x).

To do this, we only need to isolate y on the left side, and then simplificate the right side. The first step is subtracting 6 in both sides, so we get:

y = 5*(x - 4) - 6

Now we simplificate the right side:

y = 5x - 5*4 - 6 = 5x - 20 - 6 = 5x - 26

Then we conclude that:

y = f(x) = 5x - 26.

If you want to learn more about functions:

https://brainly.com/question/4025726

#SPJ2